2022
DOI: 10.1101/2022.12.13.520206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The MOV10 RNA helicase is a dosage-dependent host restriction factor for LINE1 retrotransposition in mice

Abstract: Transposable elements constitute nearly half of the mammalian genome and play important roles in genome evolution. While a multitude of both transcriptional and post-transcriptional mechanisms exist to silence transposable elements, control of transposition in vivo remains poorly understood. MOV10, an RNA helicase, is a potent inhibitor of mobilization of retrotransposons and retroviruses in cell culture assays. Here we report that MOV10 restricts LINE1 retrotransposition in mice. Although MOV10 is broadly exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Depending on the genomic and environmental contexts, genetic variation favoring one or the other primary siRNA pathway could have been selected [39][40][41][42] . Research in mammals has shown the importance of dosage of the orthologous MOV10 helicase on retrovirus silencing 43 . We showed here that natural structural variants at the eri-6/7 locus were a major driver of variation in ERGO-1 pathway activity and mRNA levels of its downstream regulated showing the most divergent eri-6/7 region based on SNVs (Fig.…”
Section: Phenotypic Effect Of the Structural Variation At Eri-6/7 On ...mentioning
confidence: 99%
“…Depending on the genomic and environmental contexts, genetic variation favoring one or the other primary siRNA pathway could have been selected [39][40][41][42] . Research in mammals has shown the importance of dosage of the orthologous MOV10 helicase on retrovirus silencing 43 . We showed here that natural structural variants at the eri-6/7 locus were a major driver of variation in ERGO-1 pathway activity and mRNA levels of its downstream regulated showing the most divergent eri-6/7 region based on SNVs (Fig.…”
Section: Phenotypic Effect Of the Structural Variation At Eri-6/7 On ...mentioning
confidence: 99%